Dithieno[3, 2-b:2′, 3′-d]pyridin-5(4H)-one-based polymers with a bandgap up to 2.02 eV for high performance field-effect transistors and polymer solar cells with an open-circuit voltage up to 0.98 V and an efficiency up to 6.84%. Issue 41 (23rd September 2015) - Hao, Minghui; Luo, Guoping; Shi, Keli; Xie, Guohua; Wu, Kailong; Wu, Hongbin; Yu, Gui; Cao, Yong; Yang, Chuluo
Abstract : Wide bandgap polymers based on DTPO were designed for high performance OFETs and PSCs. Abstract : A new electron donor, 4-(2-octyldodecyl)-dithieno[3, 2- b :2′, 3′- d ]pyridin-5(4 H )-one (DTPO ), for polymer semiconductors is reported. Its homopolymerPDTPO reveals a high hole mobility of 0.19 cm 2 V −1 s −1 in field-effect transistors. Its copolymers with benzodithiophenes (BDTO andBDTT ), namelyPDTPO-BDTO andPDTPO-BDTT, not only show wide optical bandgaps of 2.02 and 1.95 eV, but also possess deep HOMO levels of −5.38 and −5.44 eV, respectively. The polymer solar cell based onPDTPO-BDTO with an inverted architecture achieves a power conversion efficiency (PCE) of 6.84% with a high open-circuit voltage ( V oc ) of 0.93 V, while the one withPDTPO-BDTT realizes the same PCE with conventional architecture and a reasonably high V oc of 0.96 V. The PCEs are among the highest ever reported for wide bandgap PSCs. Compared to the blend withPDTPO-BDTO having the 2-ethylhexyloxy group, the one withPDTPO-BDTT having the 5-(2-ethylhexyl)thiophene-2yl- group is demonstrated to be superior as a result of faster exciton separation into free charge carriers and larger driving force for exciton dissociation, which results in high short-circuit current and V oc, respectively. The wide optical bandgaps and the excellent device performances make these polymers good candidates for boosting the PCE of the PSCs with a ternary blend layer or tandem structures.